Airborne exposure of Rhizobium to volatile organic compounds: biochemical effects on cells challenged or not by cadmium - Sá, Carina Flávia Ribeiro (2021)
Rhizobia are soil bacteria that promote the growth of legume plants. The growth and persistence of these bacteria may be limited by several factors, such as cadmium (Cd). Increasing concentrations of Cd in soil triggers different mechanisms in bacterial cells in order to tolerate stress. The production of volatile organic compounds (VOCs), resulting from the secondary metabolism of bacteria, may be a way to overcome stress situations. In this thesis the effects of five monoterpenes (α-pinene, limonene, eucalyptol, linalool and menthol) and four sulfur compounds (dimethyl sulfide (DMS), dimethyl disulfide (DMDS), dimethyl trisulfide (DMTS) and methyl thioacetate (MTA)) on growth, oxidative status and antioxidant mechanisms of Rhizobium leguminosarum E20-8 were studied, to test the hypothesis that these VOCs could influence rhizobial growth and tolerance to cadmium. The results obtained during this study showed that different compounds have different effects on Rhizobium E20-8, not being related to the chemical family to which they belong. The tested monoterpenes displayed antibacterial activity (linalool, limonene, menthol), or antioxidant properties (α-pinene and eucalyptol) in the absence of Cd. In the presence of Cd only limonene (1 and 100 mM) and eucalyptol (100 nM) were able to induce cell growth. The tested sulfur compounds generally triggered similar antioxidant mechanisms in Rhizobium. Although volatile sulfur compounds did not affect growth, they were able to reduce the oxidative stress of cells, having a membrane-protective effect (DMDS and DMTS) and thus minimizing Cd toxicity. The low concentrations of volatiles tested allow us to predict that these effects may occur in the soil ecosystem, influencing the growth and tolerance of bacterial cells whether they are under stress or not. This study contributes to better understand the effect of volatile compounds on the interactions of soil-dwelling organisms. The contribution is especially important on the influence that these compounds may have in environmental stress contexts